Drop kinetic analysis in real time by optical spectroscopy - Davies, J; Rushworth, C; Vallance, C; Cabral, J (2010)
The spatio-temporal correspondence between microchannel position and reaction 'time' permits the study of kinetics of (chemical and physical) processes with unprecedented time resolution and dynamic range [1]. Monitoring reactions in real-time with non-invasive probes remains, hitherto, a major shortcoming of microchemical drop reactors due to the minute sample volumes (pL-nL) and fast travel speeds (1-1000 mm/s). We evaluate the potential of novel microdevice fabrication via frontal photopolymerisation (FPP) [2] integrated with Cavity Ring-Down Spectroscopy (CRDS) [3] for the online analysis of individual reaction travelling droplets.